Physical and Mechanical Properties of Palm Kernel Oil-Based Polyester Polyurethane/Multi-Walled Carbon Nanotube Composites - Mat Amin, Khairul Anuar; Zailani, Muhammad Alif; Zulkifli, Nurul Nabilah; Badri, Khairiah Haji (Makara Journal of Technology, 2017)
In this study, polyurethane (PU) films from palm kernel oil-based polyester (PKO-p) incorporated multi-walled carbon nanotubes (MWNTs) are prepared via a evaporative casting method. Nanoparticle fluid dispersions containing 0.02%, 0.03%, and 0.05% wt. of MWNTs are added into PKO-p based resin and mixed by digital probe sonicator for 30 min followed by mixing with isocyanate to produce PU-MWNTs composite films. The mechanical properties, swelling, water vapour transmission rate (WVTR) and conductivity of the PU-MWNTs composite films are examined. Results show that the toughness (T) or flexibility, the tensile strength (TS), and Young’s modulus (YM) values of PU-MWNTs composite films increase with the increasing concentrations of MWNT. In contrast, the water vapour transmission rate (WVTR) and swelling test of PU-MWNTs composite films decrease with the increase of MWNT concentrations. For conductivity testing, the film with 0.05 wt.% MWNT (PU-5) has the highest conductivity value at 2.19 x 10-9 S cm-1. In summary, incorporation of MWNTs has improved the mechanical properties of the polyurethane composites films.